Os impactos econômicos de um projeto intrincado na capital paulista: a gentrificação da Cracolândia - Oliveira, Juliano Cesar Vida de (2024)
The downtown area of São Paulo, designated as the city's initial landmark, simultaneously embodies the history of the territory and serves as a portrayal of extensive hostility, especially as it is marked as the space of São Paulo's Crackland. Drawing from this heterogeneous array of notions, this elaboration establishes an analysis of a multifaceted project in the locale under consideration, particularly concerning the gentrification of this region, tracing the policies stipulated by the government since the mid-1950s to the present day, and the historical events that characterize this process, as well as examining the sociocultural and economic ramifications. Although some studies by renowned authors and the diagnosis of primary data from public institutions point to economic benefits in certain directives, negative impacts prevail, such as the expulsion of low-income residents and the elitization of revitalized areas, with policies focused on the real estate market and economic revitalization, neglecting social issues and the participation of the affected community. These programs reflect a complex interplay of political, economic, and social interests, underscoring the need for a holistic approach that considers both the tangible and implicit aspects of this phenomenon